Intermittent rivers and ephemeral streams: Perspectives for critical zone science and research on socio‐ecosystems. (4th May 2021) - Fovet, Ophelie; Belemtougri, Axel; Boithias, Laurie; Braud, Isabelle; Charlier, Jean‐Baptiste; Cottet, Marylise; Daudin, Kevin; Dramais, Guillaume; Ducharne, Agnès; Folton, Nathalie; Grippa, Manuela; Hector, Basile; et al.
Abstract: Intermittent rivers and ephemeral streams (IRES) are now recognized to support specific freshwater biodiversity and ecosystem services and represent approximately half of the global river network, a fraction that is likely to increase in the context of global changes. Despite large research efforts on IRES during the past few decades, there is a need for developing a systemic approach to IRES that considers their hydrological, hydrogeological, hydraulic, ecological, and biogeochemical properties and processes, as well as their interactions with human societies. Thus, we assert that the interdisciplinary approach to ecosystem research promoted by critical zone sciences and socio‐ecology is relevant. These approaches rely on infrastructure—Critical Zone Observatories (CZO) and Long‐Term Socio‐Ecological Research (LTSER) platforms—that are representative of the diversity of IRES (e.g., among climates or types of geology. We illustrate this within the French CZO and LTSER, including their diversity as socio‐ecosystems, and detail human interactions with IRES. These networks are also specialized in the long‐term observations required to detect and measure ecosystem responses of IRES to climate and human forcings despite the delay and buffering effects within ecosystems. The CZO and LTSER platforms also support development of innovative techniques and data analysis methods that can improve characterization of IRES, in particular for monitoring flow regimes, groundwater‐surface water flow, or water biogeochemistry during rewetting. We provide scientific and methodological perspectives for which this interdisciplinary approach and its associated infrastructure would provide relevant and original insights that would help fill knowledge gaps about IRES. This article is categorized under: Water and Life > Stresses and Pressures on Ecosystems Science of Water > Hydrological Processes Water and Life > Conservation, Management, and Awareness Abstract : The Auzon River under dry, low‐flow, and flood conditions (from left to right), which is an intermittent tributary of the Ardèche River (France), and monitored as a site of the ZA Bassin du Rhône (Rhône Bassin LTSER) and of the Mediterranean Hydro‐meteorological Observatory Cévennes‐Vivarais (OHMCV CZO).